Young student’s views of NAPLAN: impact on wellbeing through drawn responses - Roberts, Pauline; Barblett, Lennie (Frontiers in Education, 2024)
Standardised testing of academic knowledge is common in many developed countries. In Australia, the process implemented is the National Assessment Program for Literacy and Numeracy (NAPLAN). The stand-alone tests were introduced in 2008 for several educational and political reasons and since that time, the results of this assessment have been used beyond their initial purpose and bought about an unintended consequence of making the tests high-stakes. The pressure of these assessments has the potential to impact on student wellbeing, but little research has been done in this area and even less where the student's perspectives are considered. This research examined the impact of NAPLAN testing on the wellbeing of 1015 students in Years 3 and 5 across 23 school sites within metropolitan Perth in Western Australia through three iterations. This research gave students the opportunity to draw or write how they felt about NAPLAN as a participatory approach to hearing children's voices in research. This paper reports on the two-stage analysis of the 917 drawn images provided. Stage 1 analysis by two researchers categorised the images as initially positive, negative or mixed/neutral and identified the impact across the cohorts of students was not significantly negative with an average of 22.5% of the images coded as negative. Stage 2 involved detailed systematic content analysis examining the actors, locations and emotions of the drawings which indicated high levels of stress and anxiety for a small number of these students. It was evident that the tests can have a negative impact on the wellbeing of some students and this finding requires consideration by policy makers and curriculum teams engaged with writing, implementing, and assessing NAPLAN, as well as those using the results for both intended and unintended purposes.